2023
DOI: 10.1021/acs.inorgchem.3c00089
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Cadmium–Organic Framework with Dual Functions of Oxygen Evolution in Water Splitting and Fenton-like Photocatalytic Removal of Organic Pollutants

Abstract: Metal−organic frameworks (MOFs) have exhibited appreciable potential as catalytic agents in the field of material science. The research of new MOFs with dual functions in electrocatalysis and photocatalysis under ultraviolet (UV) irradiation is extremely pivotal for renewable energy applications. Hence, we synthesized a series of three-dimensional MOFs, namely, [Cd(bimb) , and [Cd(bimb) 4 (ONO 2 ) 2 ] n (Cd-MOF 3) (bimb = 1,4-bis(imidazol-1-ylmethyl)benzene; H 2 ITA = 5hydroxyisophthalic acid), with applicab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…The synthesis of a series of cadmium-based MOFs such as [Cd­(bimb) 2 (HITA) 2 ] n and [Cd­(bimb) 4 (ONO 2 ) 2 ] n revealed that the former exhibits excellent performance in OER with a lower overpotential of 279 mV and a reduced Tafel slope. In the meantime, when exposed to UV light and H 2 O 2 , these MOFs can produce OH • radicals which accelerate the breakdown of the dyes …”
Section: Insights On Mofs and Applicationsmentioning
confidence: 99%
“…The synthesis of a series of cadmium-based MOFs such as [Cd­(bimb) 2 (HITA) 2 ] n and [Cd­(bimb) 4 (ONO 2 ) 2 ] n revealed that the former exhibits excellent performance in OER with a lower overpotential of 279 mV and a reduced Tafel slope. In the meantime, when exposed to UV light and H 2 O 2 , these MOFs can produce OH • radicals which accelerate the breakdown of the dyes …”
Section: Insights On Mofs and Applicationsmentioning
confidence: 99%
“…These materials exhibit excellent characteristics for electrochemical applications because of their large specific surface area, tunable structure, porous network, high availability of metal active sites, and efficient mass-transport properties. , Therefore, they have been applied to various electrochemical processes, such as energy storage, sensing, catalysis, and electrochemical reactions . The unique properties of these compounds facilitate efficient charge transfer and ion diffusion, thereby enhancing the electrochemical performance …”
Section: Introductionmentioning
confidence: 99%
“…14 Wu and co-workers reported a series of three-dimensional (3D) MOFs with excellent oxygen evolution reaction (OER) activity and photocatalytic properties for renewable energy conversion and environmental remediation, which provided a direction for the production of multifunctional environmentally friendly catalysts. 15 Presently, many efforts have been made to modify and enhance the characteristics of single-metal MOFs by combining one or more metals into single-metal MOFs. 16 Compared with single-metal MOFs, bimetallic MOFs exhibit higher catalytic activity due to the generation of new defects within the same framework and the excellent synergistic effect between various metal centers.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al prepared a new polyoxometalate (POM)-encapsulated MOF material by the hydrothermal method, which showed excellent HER activity and dye degradation activity, but it could not be recycled . Wu and co-workers reported a series of three-dimensional (3D) MOFs with excellent oxygen evolution reaction (OER) activity and photocatalytic properties for renewable energy conversion and environmental remediation, which provided a direction for the production of multifunctional environmentally friendly catalysts . Presently, many efforts have been made to modify and enhance the characteristics of single-metal MOFs by combining one or more metals into single-metal MOFs .…”
Section: Introductionmentioning
confidence: 99%